Un algorithme de decomposition convexe pour I’ etude de structures en alliage a memoire de forme Application aux manchons de raccordement - Pagano, Stt phane; Alart, Pierre; Lebon, Frederic (European Journal of Computational Mechanics, 1998)
We presellt, in this paper, a theoretical and numerical modelisation of the coupling sleeves. The model takes into account shape memory alloys behavior, thermomechanics couplings and frictional contact. The numerical solution is based on a convex difference algorithm associated with two fixed point algorithms for thermal and frictional problems.